2016
DOI: 10.1111/trf.13659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron supplementation on iron stores and total body iron after whole blood donation

Abstract: Background Understanding the effect of blood donation and iron supplementation on iron balance will inform strategies to manage donor iron status Study Design and Methods 215 donors were randomized to receive ferrous gluconate daily (37.5 mg iron) or no iron for 24 weeks after blood donation. Iron stores were assessed using ferritin and soluble Transferrin Receptor. Hemoglobin iron was calculated from total body hemoglobin. Total Body Iron (TBI) was estimated by summing iron stores and hemoglobin iron. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 14 publications
2
59
0
Order By: Relevance
“…Actionable interventions beyond education must also be considered to protect blood donors from iron deficiency . Possibilities include extending the interdonation interval, performing ferritin testing prior to donation, and providing iron supplementation . The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actionable interventions beyond education must also be considered to protect blood donors from iron deficiency . Possibilities include extending the interdonation interval, performing ferritin testing prior to donation, and providing iron supplementation . The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…44 Possibilities include extending the interdonation interval, 45 performing ferritin testing prior to donation, 46-50 and providing iron supplementation. 49,[51][52][53][54] The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two‐thirds of donors not taking iron had not attained pre‐donation ferritin values by 24 weeks (Fig ). Analysis of the iron‐treated donors (who received iron throughout the 24‐week study period) revealed that at least 87% of iron repletion occurred within the first 8 weeks of iron therapy (Cable et al , ). Thus, daily low‐dose iron for 56‐60 days appears to be an effective strategy to replace iron lost during blood donation.…”
Section: Mitigation Of Progressive Id In Blood Donorsmentioning
confidence: 99%
“…Regardless of the dosing frequency, essentially all donors will benefit from oral iron supplements . It is important to emphasize iron is most effective in the 4 to 8 weeks immediately following donation, when its absorption is greatest …”
Section: Discussionmentioning
confidence: 99%
“…33,34 It is important to emphasize iron is most effective in the 4 to 8 weeks immediately following donation, when its absorption is greatest. 35 Cigarette smoking is associated with increased hemoglobin in the general public, 36 first-time blood donors, 37 and high-intensity blood donors. 6 The effect in first-time donors varies from 0.26 to 0.59 g/dL depending on smoking intensity.…”
Section: Discussionmentioning
confidence: 99%